Ethnobotany of ritual plants in Malay culture: A case study of the Sintang community, Indonesia - Suwardi, Adi Bejo; Zidni Ilman Navia; Imam Hadi Sutrisno; Henry Elisa; Efriani (Ethnobotany Research and Applications, 2025)
Background: The Malay community in Sintang, West Kalimantan, possesses a long-standing tradition of plant use in ceremonial and spiritual contexts. However, this knowledge is increasingly threatened by modernization and ecological degradation. This study aims to document the diversity of ritual plants used by the Malay communities of Sintang, evaluate their cultural significance, and assess the transmission of related knowledge. Methods: The study was conducted in Sintang Regency between December 2024 and January 2025. A total of 390 respondents were randomly selected for ethnobotanical surveys involving semi-structured interviews, participant observation, and plant identification. Quantitative indices, including Relative Frequency of Citation (RFC), Cultural Importance Index (CI), and Fidelity Level (FL), were applied. Results: A total of 68 ritual plant species from 43 botanical families were documented across 24 traditional rituals. The most cited species were Areca catechu (RFC = 0.928, CI = 6.02), Piper betle (RFC = 0.900, CI = 7.77), and Cocos nucifera (RFC = 0.779, CI = 3.37). Leaves (29.6%) and fruits (26.8%) were the most commonly used parts. The most diverse rituals were Sengkelan Kanong (25 species), Pesta Pernikahan (20 species), and Betangas (19 species). Two unique Sintang-specific rituals were identified: Nopen and Bepentik. A significant decline in knowledge was observed among younger generations (p = 0.0001). Conclusions: The ritual plant knowledge of the Sintang Malays reflects strong biocultural relationships. However, intergenerational erosion of this knowledge threatens cultural continuity. Community-based conservation and digital documentation are urgently needed to preserve this valuable heritage. Keywords: Ethnobotany, ritual plants, biodiversity, indigenous knowledge, West Kalimantan Abstrak Latar Belakang: Masyarakat Melayu di Sintang, Kalimantan Barat, memiliki tradisi panjang dalam pemanfaatan tumbuhan dalam konteks seremonial dan spiritual. Meskipun demikian, modernisasi dan degradasi lingkungan mengancam kelangsungan pewarisan pengetahuan ini. Penelitian ini bertujuan untuk mendokumentasikan keanekaragaman tumbuhan ritual yang digunakan oleh komunitas Melayu Sintang, mengevaluasi signifikansi budayanya, serta menilai proses pewarisan pengetahuan terkait antar generasi. Metode: Penelitian ini dilakukan di Kabupaten Sintang pada Desember 2024 hingga Januari 2025. Sebanyak 390 responden dipilih secara acak untuk mengikuti survei etnobotani melalui wawancara semi-terstruktur, observasi partisipatif, dan identifikasi spesimen tumbuhan. Indeks kuantitatif seperti Relative Frequency of Citation (RFC), Cultural Importance Index (CI), dan Fidelity Level (FL) digunakan dalam analisis. Hasil: Sebanyak 68 spesies tumbuhan ritual dari 43 famili botani terdokumentasi dalam 24 jenis ritual tradisional. Spesies yang paling sering disebut adalah Areca catechu (RFC = 0,928; CI = 6,02), Piper betle (RFC = 0,900; CI = 7,77), dan Cocos nucifera (RFC = 0,779; CI = 3,37). Bagian tumbuhan yang paling sering digunakan adalah daun (29,6%) dan buah (26,8%). Ritual dengan keanekaragaman spesies tertinggi adalah Sengkelan Kanong (25 spesies), Pesta Pernikahan (20 spesies), dan Betangas (19 spesies). Dua ritual khas Sintang yang berhasil diidentifikasi adalah Nopen dan Bepentik. Terdapat penurunan signifikan dalam pengetahuan generasi muda (p = 0,0001). Kesimpulan: Pengetahuan tumbuhan ritual masyarakat Melayu Sintang mencerminkan keterkaitan biokultural yang kuat. Namun, erosi pengetahuan antar generasi mengancam kesinambungan budaya tersebut. Diperlukan upaya konservasi berbasis komunitas dan dokumentasi digital untuk menjaga warisan berharga.